The Mediterranean and eastern Atlantic species of Spinolambrus Tan & Ng, 2007: S. macrochelos (Herbst, 1790), S. notialis (Manning & Holthuis, 1981), and S. verrucosus (Studer, 1883), with a note on the identity of Lambrus spinosissimus Osório, 1923 (Crustacea: Decapoda: Brachyura: Parthenopidae) - Tan, S.H. (2014)
10.11646/zootaxa.3753.1.8